World Bank annual report 1991 (Washington, D.C. : World Bank, 1991)
While the World Bank has traditionally financed all kinds of capital infrastructure, such as roads and railways, telecommunications, and port and power facilities, the centerpiece of its development strategy emphasizes investments that can directly affect the well-being of the masses of poor people of developing countries by making them more productive and by integrating them as active partners in the development process.
Includes index.
ne 13/03/2019
Ref
Keywords: World Bank